PENERAPAN MULTIMEDIA-TUTORIAL DALAM PEMBELAJARAN SISTEM SARAF UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS - Asep Mulyani (Scientiae Educatia: Jurnal Pendidikan Sains, 2013)
The aim of this research to know the effect of multimedia-tutorial to improve student’s critical thinking skills in human nervous system concept. This research was carried out by using quasi experimental method. The student of eleventh class at a senior high school in Garut were chosen as the subject of this research. One group of students was  given multimedia-tutorial and another one was given conventional instruction, were compared in term of their critical thinking skills. Data were collected through a paper-pencil test in multiple choice formed, and analyzed by using Mann-Whytney U Test and N-Gain. The result of this study show that there was significant effect of the multimedia-tutorial toward student’s critical thinking skills. Furthermore, the experimental class obtained higher N-gain than the control class. The average of critical thinking skills N-Gain in experimental class was 0.55 and control class was 0.38. The finding of this study suggest that multimedia-tutorial is effective to improve of critical thinking skill in human nervous system.Keywords:  Multimedia, tutorial, critical thinking skills, human nervous system.